2009
DOI: 10.1099/vir.0.013037-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel virus-associated proteins encoded by UL112–113 of human cytomegalovirus

Abstract: Evidence suggests that the products of the human cytomegalovirus (HCMV) UL112-113 genes are involved in viral DNA replication during lytic infection. A polyclonal antibody was raised against the UL112 open reading frame (ORF) to characterize its function in detail. Immunoblots utilizing the UL112 antibody identified seven distinct protein bands (p20, p26, p28, p34, p43, p50 and p84) expressed during the HCMV infectious cycle. After screening a cDNA library constructed from cells 72 h after infection with HCMV,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…2b, lanes 2, 4, 6 and 8). The p34c protein is a new finding in this study, whereas p38 was identified by proteomic analyses in our previous study (Wang et al, 2009). Our results suggest that the maitotoxin-induced protease modulates the proteolysis of UL112-113 proteins.…”
Section: Calcium Influx Elicits Proteolysis Of the Ul112-113 Proteinssupporting
confidence: 56%
See 3 more Smart Citations
“…2b, lanes 2, 4, 6 and 8). The p34c protein is a new finding in this study, whereas p38 was identified by proteomic analyses in our previous study (Wang et al, 2009). Our results suggest that the maitotoxin-induced protease modulates the proteolysis of UL112-113 proteins.…”
Section: Calcium Influx Elicits Proteolysis Of the Ul112-113 Proteinssupporting
confidence: 56%
“…Previously, we showed that the UL112-113 region produces eight cognate proteins, p20, p26, p28, p34, p38, p43, p50 and p84 (Wang et al, 2009). The p34 protein is translated from the un-spliced transcript, whereas alternative splicing yields p43, p50 and p84.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A polyclonal antibody (Ab) against UL76 was raised in this study via immunization of mice using oligopeptide amino acids 244 to 267 (CRAHGPGAQTVSASGAQGSGSQGAD). Polyclonal rabbit anti-UL112 was described previously (39). Monoclonal mouse anti-myc tag (clone 9B11), mouse anti-hemagglutinin (HA) tag (clone 6E2), anti-ubiquitin (clone P4D1), polyclonal rabbit anti-K48 linkage-specific polyubiquitin, and monoclonal rabbit anti-S5a (D17E4) antibodies were obtained from Cell Signaling.…”
Section: Cells and Virusesmentioning
confidence: 99%